CORRELATIONS OF CAROTID ARTERY STENOSIS AND CONTRALATERAL COMPENSATORY MECHANISMS IN ISCHEMIC STROKE SUBTYPES: hemodynamic analysis - Egamnazarova, Z.R.; Musayeva, Y.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Background: Carotid artery stenosis significantly affects the risk of IS by affecting cerebral blood flow. Narrowing of the carotid arteries may lead to decreased perfusion of the brain, which may provoke neurological deficits. Moreover, the body may activate compensatory mechanisms to maintain adequate cerebral blood flow despite significant narrowing of the arteries. Understanding the relationship between carotid artery stenosis and cerebral blood flow velocity is important for effective clinical decision making and patient management. Results: There were no significant differences between the 2 groups in terms of clinical characteristics of the patients included in the study. The average clinical score in patients with two subtypes of IS first day of hospitalization was 17.8±3.2 on the NIHSS scale and 4,5±0,5 on the modified Rankin scale, which corresponds to moderate to severe level of the disease. Conclusion: This study highlights the complex relationship between carotid artery stenosis and cerebral hemodynamics, which has important implications for the management and treatment of these patients.